The rPRRSV-E2 strain exhibited a low level of potential risk for virulence reversion - Jiang, Yifeng; Gao, Fei; Li, Liwei; Zhou, Yanjun; Tong, Wu; Yu, Lingxue; Zhang, Yujiao; Zhao, Kuan; Zhu, Haojie; Liu, Changlong; Li, Guoxin; Tong, Guangzhi (Frontiers in Veterinary Science, 2023)
Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) and Classical Swine Fever Virus (CSFV) are two important pathogens, which cause serious impact on swine industry worldwide. In our previous research, rPRRSV-E2, the recombinant PRRSV expressing CSFV E2 protein, could provide sufficient protection against the lethal challenge of highly pathogenic PRRSV and CSFV, and could maintained genetically stable in vitro. Here, to evaluate the virulence reversion potential risk, rPRRSV-E2 had been continuously passaged in vivo, the stability of E2 expression and virulence of the passage viruses were analyzed. The results showed that no clinical symptoms or pathological changes could be found in the inoculated groups, and there were no significant differences of viraemia among the test groups. Sequencing and IFA analysis showed that the coding gene of exogenous CSFV E2 protein existed in the passaged viruses without any sequence mutations, deletions or insertions, and could expressed steadily. It could be concluded that the foreign CSFV E2 gene in the genome of rPRRSV-E2 could be maintained genetically stable in vivo, and rPRRSV-E2 strain had relatively low level of potential risk for virulence reversion.